2022
DOI: 10.1111/jog.15363
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis of microarray data to identify hub genes, as diagnostic biomarker of HELLP syndrome: System biology approach

Abstract: Background: HELLP syndrome is one of the disorders characterized by hemolysis, increased liver enzymes and decreased platelet count. So far, many molecular pathways and genes have been identified in relation to the pathogenesis of this syndrome; however, the main cause of the incidence and progression of the disease has not been identified. Using the biological system approach is a way to target patients by identifying genes and molecular pathways. In this study, we investigated genes and important molecular f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Furthermore, MS4A4A regulated eosinophil infiltration during lung allergic inflammation induced by the intranasal administration of house dust mites [ 44 ]. Zahra et al found that HIST1H4 was involved in the pathogenesis of HELLP syndrome and was closely related to autoimmunity as one of the hub genes with the highest degree of connectivity [ 45 ]. Yue reported that the number of autoantibodies against C3AR1 decreased in pSS [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MS4A4A regulated eosinophil infiltration during lung allergic inflammation induced by the intranasal administration of house dust mites [ 44 ]. Zahra et al found that HIST1H4 was involved in the pathogenesis of HELLP syndrome and was closely related to autoimmunity as one of the hub genes with the highest degree of connectivity [ 45 ]. Yue reported that the number of autoantibodies against C3AR1 decreased in pSS [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of HELLP syndrome has not yet been fully discovered. However, the activation of endothelial cells, increased production of antiangiogenic factors and microvascular injury resulting in microangiopathic anemia, periportal hepatic necrosis, and thrombocytopenia are probably induced by the ischemia occurring in placental tissue [ 8 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%